Incidence and outcome of traumatic brain injury in paediatric population of Bosnia and Herzegovina: a single centre experience - Ibrahim Omerhodžić; Nevena Mahmutbegović; Bekir Rovčanin (Medicinski glasnik, 2019)
Aim: To evaluate the incidence, modalities of treatment and outcome in paediatric patients with traumatic brain injury (TBI). Methods: A retrospective cross-sectional study including 353 paediatric patients with head injury was carried out in the Department of Neurosurgery of University Clinical Centre Sarajevo during the period 1 July 2006-30 June 2012 (72 months). For each patient the lowest Glasgow Coma Scale (GCS) was established and the patient was accordingly classified as suffering from mild, moderate or severe TBI. Neuroimaging data included computer tomography (CT). Survival rates and method of treatment were compared according to age group, and matched with the total number of patients examined. Results: A total of 353 children with head trauma were identified. A severe TBI (GCS < 8) was found in 33 (out of 353) children, mostly in the age group 11-18. Falls were the most common cause of trauma, followed by traffic accidents. Falls were the most common mechanism in the infants, preschool, and school children up to 10 years old; children aged 11-18 showed a higher rate of traffic accidents comparing to children younger than 3 years. Of 353 patients, 49 (13,9%) required surgical procedure, 304 (86.1%) were threated conservatively. Survival rate was 96.6 %. Conclusion: The majority of hospitalized patients qualify for medical treatment and surgical intervention is reserved for selected cases. Thus, the adequate pre-hospital care is essential.
Keywords: head trauma; children; surgical management